2016
DOI: 10.1016/j.devcel.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Control of Developmental Dynamics and Plasticity

Abstract: Chromatin structure is intimately connected with gene expression and cell identity. Here we review recent advances in the field and discuss how establishment of cell identity during development is accompanied by large-scale remodeling of the epigenetic landscape and how this remodeling drives and supports lineage specification and maintenance. We discuss maternal control of the early embryonic epigenetic landscape, selective usage of enhancer clusters via 3D chromatin contacts leading to activation of transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 100 publications
0
89
0
1
Order By: Relevance
“…In the context of Waddington’s landscape, chromatin structures and regulators affect the height of the walls that partition canals in that they prevent cells from switching states. This central role for chromatin is strongly supported by genetic, cell biology and biochemistry studies (as reviewed in (17, 23, 24)). Here we highlight just a few key concepts.…”
Section: Chromatin Homeostasis and Waddington’s Landscapementioning
confidence: 91%
See 1 more Smart Citation
“…In the context of Waddington’s landscape, chromatin structures and regulators affect the height of the walls that partition canals in that they prevent cells from switching states. This central role for chromatin is strongly supported by genetic, cell biology and biochemistry studies (as reviewed in (17, 23, 24)). Here we highlight just a few key concepts.…”
Section: Chromatin Homeostasis and Waddington’s Landscapementioning
confidence: 91%
“…In embryonic stem (ES) cells, hyper-dynamic nucleosome exchange hinders the establishment of repressive structures, leaving many developmental TF genes in a ‘bivalent’ state with ‘active’ and ‘repressive’ histone marks that ‘poises’ them for alternate fates (1, 15) As developing cells commit along specific lineages, their chromatin becomes more restrictive (23, 24, 26, 3033). Progressive chromatin restriction correlates with reduction in cell fate potential and is likely to play a causal role in this regard (24, 32).…”
Section: Chromatin Homeostasis and Waddington’s Landscapementioning
confidence: 99%
“…Post-translational modifications of histones and DNA methylation regulate nucleosome compaction that facilitates or impedes TFs accessibility. For example, while histone modifications such as H3 lysine 4 mono-methylation, di-methylation and tri-methylation (H3K4me1, H3K4me2 and H3K4me3) and H3 lysine 27 acetylation (H3K27ac) facilitate TF binding and the access of the transcription machinery to DNA, DNA methylation and H3K27me3 are normally associated with reduced DNA binding access and gene repression [5].…”
Section: The Temporal and Spatial Properties Of Macrophage Regulatorymentioning
confidence: 99%
“…One of the key insights that emerged is that these mechanisms differ from those mediating canonical development and differentiation. In the latter processes, transcription factors (TFs) coordinate the orderly post-translational modification of histones to progressively specify and constrain the responsive chromatin landscape that is inherently linked to the developmental path of the respective cell [5]. While differentiated resident macrophages apparently follow this model [6 ,7 ], inflammatory macrophages resulting from acute differentiation have a pre-defined open chromatin landscape for nearly all central transcriptional regulators, irrespective of their actual transcription status [8].…”
Section: Introductionmentioning
confidence: 99%
“…Microarray analysis in chondrocytes after 30 min of dynamic compression revealed that 325 genes expression were changed, including those related to the mitogen-activated protein kinase (MAPK) and transforming growth factor-β pathways [11]. This study may help appreciation of chondrocytes responding to mechanical forces based on analysis of the overall genome, however, proteins are executors of numerous biological functions, and many factors affect the process whereby gene expression produces proteins, leading to potential inconsistencies in gene and corresponding protein expression [12]. Although the genomic method has improved our understanding of the mechanisms underlying mechanotransduction in chondrocytes, further clarification is still needed.…”
Section: Introductionmentioning
confidence: 99%